Arrangements of Fe-Centered Zn12 Icosahedra in Fe-Zn Intermetallic Compounds Determined by Ultra-High Resolution Scanning Transmission Electron Microscopy. Issue 1760 (16th January 2015) - Baker, I.; Heilmaier, M.; Kishida, K.; Mills, M.; Miura, S.; Okamoto, Norihiko L.; Yasuhara, Akira; Tanaka, Katsushi; Inui, Haruyuki
ABSTRACT The crystal structure of the Î´1p phase in the Fe-Zn system has been refined by single-crystal synchrotron X-ray diffraction combined with ultra-high resolution scanning transmission electron microscopy. The crystal structure can be described to build up with Fe-centered Zn12 icosahedra. The deformation properties obtained by single-crystal micropillar compression tests of the Î´1p phase is discussed in terms of the arrangement of the Fe-centered Zn12 icosahedra in contrast with the Î¶ phase in the Fe-Zn system.